Prevalence and Response to Needle Stick Injuries - Muhammad Alam, Hikmat Ullah Qureshi, Rashid Aslam, Sarwat Noreen, Ali Gohar Khan, Farah Deeba (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To study the prevalence and response to needle-stick injuries in a tertiary care hospital. Study design: Cross-sectional study Place and duration of study: Dept. of Gen. Surgery, Hayatabad Medical Complex Peshawar from 01-06-2020 to 30-06-2022. Methodology: One hundred and ninety three healthcare workers were recruited, including doctors, medical students, nurses, student nurses and paramedics. Results: There were 60(31.1%) healthcare workers reported needle stick injury. Majority of the injuries 51(85%) occurred during contact with patients who were assessed as not high-risk and 9(15%) when exposed to high-risk patients. Most of responders 49(81.7%) reported that the injury was self-inflicted and 11(18.3%) reported that it was caused by someone else. About 45(75%) injuries were caused by hollow bore needle and 15(25%) by a solid needle. Most of the needle stick injuries occurred at the bedside 50(83.4%), 8(13.4%) in the operating theatre and 2(3.4%) were at other locations. Conclusion: Needle stick injury is a significant cause of physical and psychological morbidity among healthcare personnel. Proper training and strict protocol for following the standard precaution can minimize its incidence. To improve its reporting the procedures of reporting a needle stick injury could be simplified. Keywords: Needle, injury, health care professional.